Attenuated and non‐haemadsorbing (non‐HAD) genotype II African swine fever virus (ASFV) isolated in Europe, Latvia 2017. Issue 3 (18th February 2019) - Gallardo, Carmina; Soler, Alejandro; Rodze, Ieva; Nieto, Raquel; Cano‐Gómez, Cristina; Fernandez‐Pinero, Jovita; Arias, Marisa
Abstract: A non‐haemadsorbing (non‐HAD) ASF virus (ASFV) genotype II, namely Lv17/WB/Rie1, was isolated from a hunted wild boar in Latvia in 2017. Domestic pigs experimentally infected with the non‐HAD ASFV developed a nonspecific or subclinical form of the disease. Two months later, these animals were fully protected when exposed to other domestic pigs infected with a related virulent HAD genotype II ASFV.